Long-term outcomes of patients with pulmonary arteriovenous malformations considered for lung transplantation, compared with similarly hypoxaemic cohorts - Shovlin,CL; Buscarini,E; Hughes,JMB; Allison,DJ; Jackson,JE (BMJ Open Respiratory Research, 2017)
INTRODUCTION:Pulmonary arteriovenous malformations (PAVMs) may not be amenable to treatment by embolization or surgical resection, and many patients are left with significant hypoxemia. Lung transplantation has been undertaken.There is no guidance on selection criteria.METHODS:To guidetransplantation listingassessments, the outcomes of the six patients who had been considered for transplantation were compared to a similarly hypoxemic patient group recruited prospectively between2005-2016at thesame UK institution.RESULTS: Sixpatientshad been formally considered for lung transplantation purely for PAVMs. One underwent a single lung transplantation for diffuse PAVMs and died within 4 weeks of surgery. Theother five were not transplanted, in four cases at the patients’ request.Their current survival ranges from 16-27 (median 21) years post transplant assessment. Of 444 consecutive patients with PAVMs recruited between 2005-2016, 42 were similarly hypoxemic to the “transplant-considered”cohort (SaO2 <86.5%). Hypoxemic cohorts maintained arterial oxygen content through secondary erythrocytosis and higher haemoglobin. The “transplant-considered” cohort had similar CaO2to the hypoxemic comparator group,but higher MRC dyspnea scores(p=0.023),higher rates of cerebral abscesses (p=0.0043) and higher rates of venous thromboemboli (p=0.0009) that were evident before and after the decision to list for transplantation. CONCLUSIONS: The non-transplanted patients demonstrated marked longevity. Symptoms and co-morbidities were better predictors of health than oxygen measurements. While a case-by-case decision, weighing survival estimates and quality of life will help patients in their decision making, the data suggesta verystrong case must be made before lung transplantation is considered.